2020
DOI: 10.1101/2020.05.29.20116202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Circulating Tumor-specific DNA Methylation Markers in the Blood of Patients with Pituitary Tumors

Abstract: Genome-wide DNA methylation aberrations are pervasive and associated with clinicopathological features across pituitary tumors (PT) subtypes. The feasibility to detect CpG methylation abnormalities in circulating cell-free DNA (cfDNA) has been reported in central nervous system tumors other than PT. Here, we aimed to profile and identify methylome-based signatures in the serum of patients harboring PT (n=13). Our analysis indicated that serum cfDNA methylome from patients with PT are distinct from the counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Currently, however, separate techniques are required for these analyses, and so, DNA quantity and total number of molecules of interest become limiting. Rather than purely detecting the presence of cancer DNA, epigenomic marks associated with the cell of origin could be also leveraged to improve detection and classification of pathologies [32,56]. A recent study examining CpG sites identified up to 2% of brain-derived cfDNA in the circulation of healthy individuals [57].…”
Section: Sampling the Cerebrospinal Fluid As A Liquid Biopsymentioning
confidence: 99%
“…Currently, however, separate techniques are required for these analyses, and so, DNA quantity and total number of molecules of interest become limiting. Rather than purely detecting the presence of cancer DNA, epigenomic marks associated with the cell of origin could be also leveraged to improve detection and classification of pathologies [32,56]. A recent study examining CpG sites identified up to 2% of brain-derived cfDNA in the circulation of healthy individuals [57].…”
Section: Sampling the Cerebrospinal Fluid As A Liquid Biopsymentioning
confidence: 99%